Recruitment Strategies and Union Exclusion in Two Australian Call Centres - Broek, Diane (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryRecruitment processes are seen as critical to the success of contemporary organizations and integral to human resource practices, particularly in those firms setting up greenfield operations or undertaking organizational change programs. This article analyses the recruitment methods used in several large call centres in the Australian telecommunications industry. It particularly focuses on the issue of how recruitment was explicitly or implicitly designed to recruit customer service representatives who might be antithetic to workplace trade unionism. Three processes are identified. These include the use of sophisticated recruitment processes which identify those with unitarist tendencies, identifying and excluding, or blacklisting, those with union backgrounds or those who previously worked in highly unionized firms and lastly applying pressure on recruits to sign individual non-union contracts at the appointment or promotion stage.